Digitally reconstructed radiographs from abdominal CT scans as a new tool for radiotherapy planning - Bahner, Malte Leonardo; Debus, Jürgen; Zabel-du Bois, Angelika; Levegrün, Sabine; Kaick, Gerhard van (Investigative radiology, 1999)
OBJECTIVE. - Abdominal extended field radiotherapy requires exact field shaping. Conventional treatment planning is difficult to adapt to individual anatomy, whereas three-dimensional planning is time-consuming. The authors introduce a method with digitally reconstructed radiographs of spiral CT data to facilitate radiotherapy planning. - METHODS. - Twenty-two patients underwent imaging with a standardized CT protocol, and digitally reconstructed radiographs were calculated in central beam projection using a maximum intensity projection algorithm (MIP-DRR). For comparison, the expected error from parallel projection was calculated depending on object thickness and field length. - RESULTS. - The contrast-enhanced protocol used in spiral CT produces a good rendition of all relevant structures. The resulting MIP images have a geometry identical to standard simulation films and to the linear accelerator, whereas standard MIPs with parallel projection show significant distortion compared to the treatment process. - CONCLUSIONS. - Because of the integration of the geometry of the radiotherapy treatment, the described central beam projection method might be used as a new tool for abdominal radiotherapy planning. The CT protocol offers sufficient contrast enhancement in all relevant structures and provides all necessary anatomic information for individual beam shaping.